SOSIALISASI PEMANFAATAN WORKSHEET MATEMATIKA SEBAGAI MEDIA BIMBINGAN BELAJAR DI DESA SELOREJO - Rachmawati Rachmawati (JPM PAMBUDI, 2022)
Education is the main factor to improve Human Resources (HR). The level of education in a person will affect the pattern of life of that person. Education is basically not just general knowledge or other words formal education, but education can be obtained through tutoring carried out in student environment. The purpose of tutoring is to help students who experience difficulties in learning during formal school hours and also for develop the potential of each student. One of the media used is a worksheet. The use of worksheets will make it easier for students to understand the material or subjects mathematics. In this regard, the Center for Research and Community Service (P2M) IKIP Budi Utomo Malang with Firda Alfiana Patricia as resource person assisted by Rachmawati, and Kenys Fadhilah Zamzam held tutoring to create a smart generation for elementary school students in RT 5 Selorejo Village. The activity is carried out in March – April 2021 with the agenda of socializing the use of math worksheets as a medium of learning guidance for elementary school students